The Surgeon Mentor Program: Outcomes of Total Hip Arthroplasty via the Direct Anterior Approach - Jiang, Melinda; Inglis, Mark; Morris, David; Eardley-Harris, Nathan; Wilson, Christopher J. (The Journal of Hip Surgery, 2021)
The direct anterior approach (DAA) for total hip arthroplasty has been increasing in popularity due to potential benefits including less pain, faster recovery, decreased risk of dislocation, and a reduced length of stay. The DAA has been described by many to have a steep learning curve owing to its greater risk of complications when first using the approach. The primary aim of this study was to design and implement a specific surgeon mentor program in an attempt to reduce the learning curve of the DAA. Surgeons completed the surgical education and mentoring program designed to reduce the initial increase in complication rate when first learning the DAA in a public hospital setting. A retrospective review of clinical and radiological outcomes on the first 67 cases was then conducted. Of these, 43 cases were eligible for inclusion. The 43 patients in this study had a mean age of 66.7, BMI of 26.7, and 57% of them were female. Follow-up was between 39 and 49 months, with a mean of 46 months. There were no fractures, dislocations, or blood transfusions. One patient required revision for deep infection. The mean length of stay was 2.81 days. At 6 weeks postoperative, 86% were independently mobile, 9.3% were using a cane, and 4.7% were being weaned off a walker. The radiological assessments found a mean cup abduction of 39.9 ± 5.1 degrees, mean femoral offset of 1.6 ± 5.5 mm, and a total hip offset of 1.3 ± 7 mm greater than the contralateral hip. Patients had a mean leg length discrepancy of −0.9 ± 5.9 mm. In conclusion, a surgeon mentoring program was designed and implemented to reduce the learning curve of the DAA in our center, with satisfactory 3-year clinical and radiological outcomes achieved. This study provides preliminary support for the potential utility of the mentoring program in facilitating other centers in safely introducing the DAA into their practice without an initial increase in complication rate.
Keywords: total hip arthroplasty; learning curve; direct anterior approach; Smith-Peterson; mentor